The effect of talent management on turnover intention mediated by employee engagement - Sinta Sundari Heriyanti; Raniasari Bimanti Esthi (International Journal on Social Science, Economics and Art, 2023)
This study aims to determine the effect of talent management on turnover intention, that mediated by employee engagement. The population in this study were employees of the millennial generation aged 25-39 years and Z generation aged 19-24 years who worked in automotive / automotive spare part companies in the Bekasi Industrial Area with a total sample of 132 respondents. The data collection method uses an e-questionnaire through the Google form and the results of data analysis use Smart PLS. The results of the structural equation model analysis show that talent management has a significant positive effect on turnover intention, and this effect is mediated by employee engagement. These findings indicate that organizations must have an effective talent management strategy that can increase employee engagement to reduce turnover intention.